Study on the Stability and Control of Gob-Side Entry Retaining in Paste Backfill Working Face - Changtao Xu; Xiangyu Wang; Dingchao Chen; Guanghui Wang; Zhenpeng Niu; Huixing Lu (Applied Sciences)
Due to the poor stability of the roof and floor of the roadway in the 3-1 coal seam of Chahasu Coal Mine, traditional gob-side entry retaining (GER) methods fail to meet the production safety requirements. To address this, a GER technology using paste backfill was proposed. This study reveals the stability mechanism of the surrounding rock in GER with paste backfill through theoretical analysis, numerical simulation, and industrial experiments. First, theoretical analysis was conducted to determine the overburden movement characteristics under varying backfill ratios. Uniaxial compressive tests on the paste material demonstrated that its bearing capacity reaches a relatively stable state after 14–28 days of curing. Second, numerical simulations were performed to study the deformation patterns of the surrounding rock and mine pressure characteristics under backfill ratios of 65%, 75%, 85%, and 95%. The Strain-Softening model was used to calibrate the backfill material parameters. The results showed that as the backfill ratio increased, the support provided by the backfill material improved, leading to enhanced bearing capacity of the overlying strata, reduced mine pressure intensity, significantly decreased deformation of the roadway, and substantially improved stability of the surrounding rock. Third, under a backfill ratio of 95%, the evolution of the abutment stress during face advancement was investigated. It was found that as the working face advanced, the backfill material and the overlying strata gradually formed a stable composite structure, with the abutment stress in the mining area stabilizing over time. Finally, to address the issue of insufficient initial strength and limited support capacity of the paste backfill material, a comprehensive control system for surrounding rock stability was proposed. This system integrates a basic bolt-mesh-cable support structure with localized reinforcement using portal hydraulic supports. Field industrial practices demonstrated that after applying this comprehensive control technology, the convergence of roof and floor was approximately 190 mm and the convergence of two ribs was about 140 mm, effectively ensuring the stability of surrounding rock in GER with paste backfill working face.